Acute pulmonary edema due to hypoxia during a difficult intubation in a rheumatoid arthritis patient - Jeong, Ji Seon; Jun, Jong Hun; Song, Hyo Jin; Choi, Sung Hwan (Korean journal of anesthesiology, 2014)
KCI Citation Count: 0